USING AQUEOUS TWO-PHASE SYSTEM COMBINED WITH ISOPROPANOL PRECIPITATION FOR ISOLATION OF PLASMID DNA FROM ALKALINE LYSATE - Ataci, Nese; Arisan, Inci (YILDIZ TECHNICAL UNIV, 2010)
This work presents a study of the partitioning of a plasmid from alkaline lysate in polyethylene glycol (PEG) / ammonium sulfate aqueous two-phase system (ATPS). The aqueous two-phase extraction system was prepared with a 35 % w/w PEG 600, 6 % w/w ammonium sulfate and 20 % w/w of lysate load. The performance of this process was determined by qualitative assays. Qualitative analysis was realized by using 1 % of agarose gel electrophoresis. PEG 600 (35% w/w) - (NH4) 2SO4 (6% w/w) system recovered total amount of plasmid with small amount of RNA in bottom phase. In addition, the bottom phase of the system was integrated with 2-propanol precipitation step. Plasmid yield and RNA profile were observed for the use of different 2-propanol concentrations. Finally, maximized plasmid yield was obtained at 0,7 (v/v) 2-propanol concentration. In higher concentrations than 2-propanol of 0,7 (v/v) plasmid yields were decreased, and in this case plasmid was removed together with RNA in supernatant.
Keywords: Plasmid DNA; plasmid isolation; aqueous two phase systems; gene therapy; 2-propanol precipitation; Engineering